İnsan Ticareti ve Sosyal Hizmet - Çay, Murat (Göç ve Sosyal Hizmet, 2023)
Migration and human trafficking cause social injustices and human rights violations all over the world, and are a cause and consequence of important problems directly related to social work. Human trafficking is a crime that has a lasting and profound impact on the lives of society and individuals. These effects include physical, psychological, social and economic problems and harm the social structure of the society as well as the victims. Migration and human trafficking are often intertwined phenomena. Human trafficking particularly affects vulnerable groups such as women, children and forced laborers and leads to human rights violations. International cooperation, awareness-raising, development of qualified policies and active participation of social workers in the process are important points in the fight against human trafficking. Social work plays an important role in combating human trafficking and the problems posed by human trafficking and strives to eliminate the causes of human trafficking, assist victims, and achieve social justice. Social workers play an important role in protecting the rights of immigrants and reducing their vulnerability to trafficking. At the same time, social workers should raise public awareness of human trafficking and migration and strive to prevent these problems. On this basis, it is essential for social work to achieve its goals by ensuring that we create a world that is more fair and respectful of human rights. This part of the book examines the phenomenon of human trafficking in the context of social work, after touching on important points about human trafficking and migration. Human trafficking is at an indispensable point in terms of ensuring the well-being of all individuals and fulfilling the purposes of social service.In the chapter, human trafficking is discussed under topics such as social work education and case management in social work. Information about the difficulties experienced in identifying human trafficking victims and working with human trafficking victims is included. In the following sections, the political context regarding human trafficking has been tried to be explained and important legislation regarding human trafficking has been listed.